Atmospheric heat source/sink dataset over the Tibetan Plateau based on satellite and routine meteorological observations. Issue 2 (3rd April 2018) - Duan, Anmin; Liu, Senfeng; Zhao, Yu; Gao, Kailun; Hu, Wenting
ABSTRACT: The Tibetan Plateau (TP), acting as a large elevated land surface and atmospheric heat source during spring and summer, has a substantial impact on regional and global weather and climate. To explore the multi-scale temporal variation in the thermal forcing effect of the TP, here we calculated the surface sensible heat and latent heat release based on 6-h routine observations at 80 (32) meteorological stations during the period 1979–2016 (1960–2016). Meanwhile, in situ air-column net radiation cooling during the period 1984–2015 was derived from satellite data. This new dataset provides continuous, robust, and the longest observational atmospheric heat source/sink data over the third pole, which will be helpful to better understand the spatial-temporal structure and multi-scale variation in TP diabatic heating and its influence on the earth's climatic system.